Reformasi Administrasi Publik dalam Berbagai Perspektif - Hamdan (Jurnal Aplikasi Manajemen, 2009)
State Administration Reformation, these days becoming more focus. There are two twinning issues in government apparatus activity in most developing country. Fist, government bureaucracy supposed as a big boat able to save all society citizen entirely from political and also economic floods "disaster". Second, government bureaucracy often show unpleasant symptom. The lack of this administration will not be viewed as bad situation, id the confusion condition of this state administration does not spread to whole country. Administration reformation meant to develop a governance organization having efficient, adaptive, and responsive characters. Efficacy of failure of administration reformation very depend on change agent, support and commitment from political leader, social and economic environment and also right time.